Prevalence of clinical and subclinical mastitis in smallholder dairy farms in Kiambu, Kenya - Hansen, N.S.; Jensen, R. (University of Copenhagen, 2023)
In Kenya, mastitis is a major challenge, causing production losses and excessive antibiotic use. Early detection and correct mastitis treatment are crucial for the cow's recovery, thus increasing animal health welfare and minimizing economic losses for the farmer. There is a general lack of proper diagnosis, relevant knowledge, and resources in smallholder dairy farms in Kenya, leading to self-diagnosis and treatment. This results in indiscriminate or unnecessary use of antibiotics, affecting the development of antimicrobial resistance (AMR), a major global public health issue. A simple, rapid, on-farm test accessible to farmers is needed to guide initial treatment decisions. This study investigates the current mastitis management and estimates the apparent prevalence (AP) of mastitis in smallholder dairy farms in the Githunguri sub-county in Kiambu, Kenya. The distribution of four specific mastitis pathogens is determined. This study further evaluated the California Mastitis Test (CMT) to detect mastitis and the Point of Cow test (POC-t) to detect bacteria in milk samples. Lastly, this study explores the POC-t’s adoptability by dairy farmers and animal health service providers (AHSPs) in Kenya. This was done by visiting 42 farms, administering mastitis management questionnaires, and collecting milk samples from 124 randomly selected cows. Smallholder dairy farmers generally know the importance of housing practices, but the results suggest opportunities for improvement regarding milking hygiene techniques and control methods of mastitis. This study found the APs of clinical mastitis based on CMT and clinical signs at 6.5% and 14.3% and the APs of subclinical mastitis based on CMT at 50.0% and 69.0% at the cow and farm levels, respectively. The APs of clinical mastitis based on somatic cell count (SCC) and clinical signs were 6.8% and 16.7%, and the APs of subclinical mastitis based on SCC were 63.6% and 90.0% at the cow and farm levels, respectively. Based on clinical signs alone, the APs were 8.0% and 14.3% for clinical mastitis at the cow and farm levels, respectively. Streptococcus agalactiae was the most isolated target pathogen in 94.9% of positive samples. The calculated sensitivity (Se), specificity (Sp), and accuracy (Ac) of the CMT were 58.2%, 96.9%, and 80.1%, respectively, and for POC-t, 47.5%, 79.1%, and 56.5%, respectively. There was an interest in using the POC-t among farmers and AHSPs. The findings suggest a need for additional POC testing in low- and middle-income countries as the POC-t can potentially support the development of treatment guidelines in Kenya.